Interrogating social capital Indian experience - Jayal, Niraja Gopal (ed); Mohapatra, Bishnu N. (ed); Bhattacharyya, Dwaipayan (ed); Bhattacharyya, Dwaipayan (ed) (New Delhi SAGE Publications, 2004)
Social capital, Panchyats and grassroots democracy